(untitled) (Modern education and development, 2025)
In the modern era of globalization and digital transformation, the use of information and communication technologies (ICT) in language education has become both widespread and essential. Digital platforms, mobile applications, artificial intelligence, and interactive learning tools have revolutionized the way languages are taught and learned. These innovations provide learners with greater flexibility, individualized instruction, access to authentic materials, and multimodal approaches that enhance the development of all four language skills — listening, speaking, reading, and writing. One of the key advantages of modern technology in language education is the ability to adapt lessons to each learner’s pace, needs, and interests. It also increases motivation and engagement through gamification, multimedia content, and real-time feedback. Moreover, it facilitates distance and self-directed learning, making language acquisition more accessible to a wider audience. However, these benefits are accompanied by notable challenges. Over-reliance on digital tools can reduce real-life communication and may cause learners to become passive. Not all teachers and students possess equal levels of digital literacy, and technical issues or limited access to stable internet can hinder the learning process. Furthermore, the abundance of digital resources may lead to cognitive overload if not properly managed by educators. Educators should be trained to use these tools effectively to ensure meaningful and sustainable learning outcomes.